Traffic assignment paradox incorporating congestion and stochastic perceived error simultaneously. Issue 2 (2nd January 2019) - Yao, Jia; Cheng, Zhanhong; Dai, Jingtong; Chen, Anthony; An, Shi
ABSTRACT: This paper analyses the effects of congestion and stochastic perceived error in stochastic traffic assignment paradox, by the measure of both actual and perceived travel cost. Two different circumstances are studied: improving an existing link and adding a new link. It is found that different congestion cost functions and perceived error levels will significantly affect the road condition and the demand level under which paradox happens. Moreover, how the interaction between traffic demands of different O-D pairs affects the occurrence of traffic paradox is illustrated by a two O-D pairs' network. Besides, a counter-intuitive phenomenon when less stochastic perceived error yet increases the average travel cost (information paradox) is also discussed. The results of this paper help to understand the interactional impact of congestion and stochastic perceived error, and give some new insights to traffic paradox.